Extracellular superoxide dismutase in human tissues and human cell lines. - Marklund, S L (1984)
Extracellular-superoxide dismutase is a tetrameric copper-containing glycoprotein that previously has been demonstrated to be the major superoxide dismutase of human extracellular fluids. The occurrence of this enzyme in various human tissues that were removed from two accidental death victims and in 19 different human cultured cell lines was determined. All investigated tissues were found to contain extracellular-superoxide dismutase. There was a larger variation between tissues in the concentration of this enzyme than in CuZn superoxide dismutase and Mn superoxide dismutase. No relation could be demonstrated between the content of extracellular-superoxide dismutase and the content of the other superoxide dismutase isoenzymes in the various tissues. In uterus there was more extracellular-superoxide dismutase than Mn superoxide dismutase, but in all other tissues the content of extracellular-superoxide dismutase was lower than the content of the other isoenzymes. The concentration of extracellular-superoxide dismutase was higher in all investigated human tissues than in human plasma. 19 human cultured cell lines were found to be devoid of or to contain very little extracellular-superoxide dismutase. Most tissues contained more extracellular-superoxide dismutase than did the investigated cell lines.